Kontinuitas dan Transformasi Penistaan Agama: Gerakan Sosial Islam Pra-Kemerdekaan - Juma Juma (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
This research analyses the blasphemy the authors of Djawi Hisworo, Swara Oemoem and Madjalah Bangoen have done by observing the social history of Islam. Emile Durkheim's concept of mechanic solidarity is used to describe the blasphemy based on the spirit of religion. Where, the religion (Islam) has become a bond between followers, even though it has different traditions and habits. The social psychology approach to describes organizations or elites advises on have succeeded in mobilizing people to protest against religious politicians. Blasphemy, both past and today, makes people united under the issues of religion. The difference is that in the past, the “blasphemy voice” is more congregation, while today, blasphemy is more politically-pragmatic in the interests of electoral politics. The solidarity which was formed from blasphemy of religion later becomes the congregation (Islam), whereas today, it forms solidarity based on political sectarian.Keyword: Newspapers, Blasphemy, Solidarity, Religion-Political RelationsPenelitian ini mengkaji penistaan agama yang dilakukan oleh penulis Djawi Hisworo, Swara Oemoem dan Madjalah Bangoen dengan pendekatan sejarah sosial umat Islam. Teori solidaritas mekanik Emile Durkheim digunakan untuk menganalisis protes atas penistaan berbasis semangat agama. Di mana, agama (Islam) telah menjadi unsur pengikat antara pengikutnya, walau pun memiliki tradisi dan kebiasaan yang berbeda-beda. Pendekatan psikologi sosial untuk melihat organisasi atau elit yang menggerakkan umat menyuarakan protes terhadap penista agama. Penistaan agama, baik masa lalu atau masa kini sama-sama membuat umat bersatu di bawah isu agama. Perbedaannya, di masa lalu, “suara penistaan agama” lebih bersifat keummatan, sementara hari ini, penistaan agama lebih bernuansa politis-pragmatis demi kepentingan politik elektoral. Solidaritas yang terbentuk dari penistaan agama di masa lalu bersifat keummatan (Islam), sedangkan hari ini, berupa solidaritas berbasis politik sektarian. Kata Kunci: Surat Kabar, Penistaan Agama, Solidaritas, Relasi Agama-Politik